Access to Debt Finance: Which Policies Work? Empirical Evidence from Sub-Saharan Africa - Senyo Koto, Prosper (Journal of Reviews on Global Economics, 2016)
Are the structural policy reforms effective in reducing debt financing constraints on formal sector enterprises in sub-Saharan Africa? We do not know. And the reason is the relatively limited research on the effectiveness of policies in the credit market. Using policy variables from the World Bank and the Enterprise Surveys data, the analysis involves three-way error component models. The results are indicative that taken together; structural policy reforms reduce debt financing constraints, at least, as it pertains to working capital needs. There is heterogeneity in the results. Changes in the business regulatory environment benefit large firms more than small ones. Financial sector reforms affect enterprises of all sizes relatively equally. For all the twelve countries, together, trade sector reforms initially increase the likelihood of access to debt finance by 20 percent until a policy threshold, beyond which progressive reforms in the trade sector reduce the probability by as much as 13 percent. Also, not all countries experience the same effects from trade sector reforms. The result is robust to different indicators of credit constraint and measures of structural reforms. The results have implications on the World Bank’s push towards reforms on trade policy across countries.